Modelling Managerial Determinants for Green Building Technology Adoption: A Decision-Making Framework from the West Bank - Ramiz Assaf; Mohammad Qalalweh; Abdalmuttaleb Al-Sartawi; Zaher Abusaq; Mohammad Kanan (Decision Making: Applications in Management and Engineering, 2024)
This research explores the managerial and environmental conditions affecting the uptake of Green Building Technology (GBT) in the West Bank, based on data collected from 500 real estate developers. The analysis employed Partial Least Squares Structural Equation Modelling (PLS-SEM) to evaluate the proposed framework. The results demonstrate that governmental support, the perceived benefits of GBT, acceptance within the market, and societal pressures all significantly and positively influence adoption. Conversely, perceived limitations of GBT show a significant negative impact. Additionally, the presence of internal GBT-related resources within organisations mediates the effect of government support on adoption. Leadership commitment from top management and a strong sense of environmental responsibility were also found to strengthen several of the model’s relationships. The findings emphasise the importance of both institutional backing and internal capacities in driving sustainable building practices, alongside the active participation of key stakeholders. This study enhances the academic discourse on green building and provides practical guidance that may assist policymakers, property developers, and sustainability advocates in promoting GBT implementation within the context of developing nations